Asymmetric Intramolecular Oxa‐Michael Reactions of Cyclohexadienones Catalyzed by a Primary Amine Salt1. Issue 6 (20th December 2012) - Wu, Wenbin; Li, Xin; Huang, Huicai; Yuan, Xiaoqian; Lu, Junzhu; Zhu, Kailong; Ye, Jinxing
<x xml:space="preserve">Abstract</x> Michael brings the rings: An asymmetric intramolecular oxa‐Michael reaction involving iminium activation has been developed. This reaction provides enantioenriched 1, 4‐dioxane derivatives with up to 99 % yield and 98 % ee. The method allows for concise and stereoselective access to stereodiverse, complex tetracyclic compounds containing a bicyclo[2.2.2]octan‐2‐one backbone with multiple chiral centers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>